Factors associated with depressive disorder among Peruvian older adults - Torres Mantilla, Juan Carlos (2023)
Objective: To determine the prevalence and factors associated with depressive disorder among Peruvian older adults over 60 years of age.Materials and methods: An observational, analytical and cross-sectional study was conducted based on a secondary analysis of the 2019 Encuesta Demográfica y de Salud Familiar (ENDES - National Demographic and Family Health Survey),administered at national level by Instituto Nacional de Estadística e Informática del Perú (INEI - National Institute of Statistics and Informatics of Peru). The sample consisted of 4,174 older adults. The main variable was suffering from a depressive disorder (depressed/not depressed) and the independent variables were age, sex, educational level, wealthquintile (classified into five levels of wealth), area of residence (classified as urban/rural), geographic domain (classified as Lima Metropolitan Area, the rest of the coast, the highlands and the jungle), health coverage (classified as insured/uninsured), alcohol consumption (yes/no), smoking (yes/no) and presence of a disability (yes/no). Analyses of absoluteand relative frequencies, differences in proportions and a multivariate analysis using generalized linear models (GLM) were performed.Results: The prevalence of depressive disorder and disability accounted for 13.18 % and 7.86 %, respectively. Older males were less likely to suffer from a depressive disorder (PRa = 0.602; 95 % CI: 0.513-0.706) than females, and the group over85 years of age showed a higher risk than those from 60 to 74 years (PRa = 1.664; 95 % CI: 1.304-2.124). Besides, not presenting a disability behaved as a preventive factor (PRa = 0.542; 95 % CI: 0.440-0.668), while a higher educational level and wealth quintile, starting from the “Middle” quintile, were protective factors when taking the categories "No education" and "The poorest" as reference, respectively (p < 0.005). Conclusions: Belonging to the group over 85 years of age, being a female, being in lower wealth quintiles, suffering from a disability and having a lower educational level were risk factors for depressive disorder among Peruvians older adults.